Socio-environmental Factors Impacting on Teachers’ Attitudes Towards Code-Switching in ESL Classrooms in a Rural District in Malaysia - Tan Nam Siong; Low Hui Min (Kajian Malaysia, 2017)
Code-switching is common in certain English as Second Language (ESL) classrooms in Malaysia. In this study, a survey method was used to account for the impacts of macro-level socio-environmental factors such as school type, school size and class size on ESL teachers' attitudes towards classroom codeswitching. The results showed that in general, teachers reported positive attitudes towards classroom code-switching in relation to teachers' persona, subject access, classroom management and interpersonal relationships. Correlation and regression analyses showed that teaching experience was a significant predictor of teachers' attitudes towards classroom code-switching in relation to teachers' persona; while the matching of teachers' and students' ethnicity was a significant predictor of teachers' attitudes towards classroom code-switching in relation to interpersonal relationships. The findings contributed the insights that different socio-environmental factors provided explanations for different aspects of teachers' attitudes towards classroom code-switching. The interplay of factors affecting teachers' attitudes on classroom code-switching is multidimensional and should only be interpreted by considering all possible factors involved.